Framing the Ultimate Fighting Championship: an Australian media analysis. Issue 7 (8th August 2016) - Gaarenstroom, Thomas; Turner, Paul; Karg, Adam
Abstract: Reporting about combat sports generates much discussion within the broader community. Many opinions abound and views impact on the acceptance of these types of sports in society. Within Australia, the introduction of Ultimate Fighting Championship (UFC) contests has generated significant debate. This debate has been presented in the media reflecting political, social and moral arguments about the value or social acceptance of this sporting activity. This research explores the manner in which the media frames the reporting into UFC in Australia. A process for framing newspaper articles is broken down and adopted through analysis of 68 articles drawn from two major Australian National newspapers. Themes that emerged included Defining and Legitimizing the Sport, Growth and Economic Benefit, Image and Impact on Society and Political and Government Factors. Upon establishing these themes, it was apparent these presented a Conflict Frame.